Effect of initial ph to the production of the thermostable cellulase by aspergillus fumigatus in solid state fermentation using oil palm frond / Ummi Nasrah Talib - Talib, Ummi Nasrah (Faculty of Applied Sciences, 2015)
Cellulases are the group of hydrolytic enzymes, capable of degrading all types of lignocellulosic materials. Cellulases have the wide range of applications. Present study was carried out to study the thermostable cellulase enzyme production ability of Aspergillus fumigatus against the lignocellulosic bio-waste like oil palm frond as the substrate under solid state fermentation at 50 ˚C in different initial pH levels, pH (5, 7 and 9). The enzyme activity was measured by using FPase assay every 24 hours for 10 days. In this study, the highest level of enzyme activity was obtained at pH 5.0 followed by pH 7.0 and the least was obtained at pH 9.0. This indicates that alkaline medium is not suitable for A. fumigatus development. It was therefore concluded that A. fumigatus is able to produce high amount thermostable cellulase at pH 5.0 in solid state fermentation using oil palm frond as the substrate.